Effects of histamine, ethanol, and a detergent on exudation and absorption across guinea pig airway mucosa in vivo. Issue 10 (October 1991) - Greiff, L; Erjefält, I; Wollmer, P; Pipkorn, U; Persson, C G
Abstract : This study examined effects of three substances that cause mucosal provocation (histamine, ethanol, and the detergent dioctylsodium sulphosuccinate (DOSS] on the flux of solutes across airway vascular mucosal barriers in anaesthetised guinea pigs. The inward flux was assessed as absorption of iodine-131 labelled albumin (MW 69, 000) from the tracheobronchial surface into the circulation and the outward flux as the exudation of two intravenously administered plasma tracers–125I albumin (MW 69, 000) and fluorescein isothiocyanate conjugated (FITC) dextran (MW 70, 000)–into the airway. The absorption of technetium-99m labelled DTPA (MW 492) from the tracheobronchial airways was determined in separate experiments. Histamine (5.0 nmol) dissolved in 40 microliters saline and superfused on the tracheobronchial mucosal surface caused significant and similar entry of 125I albumin and FITC dextran into the airway lumen. This dose of histamine did not, however, alter the absorption of small (99mTc DTPA) or large (131I albumin) solutes across the airway mucosa. Ethanol (0.17 mumol), superfused in the same way, also caused significant exudation of the plasma tracers into the airway lumen. In addition, ethanol increased the absorption of 131I albumin without causing change in the disappearance rate of 99mTc DTPA. The detergent, DOSS (0.28 nmol), dissolved in ethanol (0.17 mumol), caused a pronounced increase in exudation and much increased absorption of small and large tracer solutes. Thus three patterns of change in airway mucosal barriers were found. The agents that are toxic to membranes, ethanol and DOSS, caused a bidirectional increase in permeability across the mucosa, whereas histamine caused only an outward exudative flux. The results obtained with histamine are similar to those seen previously with bradykinin, capsaicin, and allergen, suggesting that endogenous inflammatory mediators have a role in mucosal defence, producing entry of plasma exudates into the airway lumen without increasing the mucosal absorption of luminal material.